(untitled) (Nigerian Journal of Technology, 2021)
This study investigated the effects of temperature, pre-treatment and slice thickness on the effective moisture diffusivity and activation energy of tannia (Xanthosoma sagittifolium) cormels. White-fleshed and pink-fleshed varieties of the cormels were used for this study. The effective moisture diffusivity and activation energy of fresh and blanched cormels were determined by drying them at three temperature levels (60, 70 and 80°C) and three slice thicknesses (2, 3 and 4 mm). The effective moisture diffusivity and activation energy of the cormels ranged between 1.47×10-7 and 2.09×10-7 m2 s-1 and 49.02 and 63.23 kJ mol-1 respectively. The study established that the effective moisture diffusivity and activation energy are drying temperature dependent. The effects of pre-treatment and slice thickness were also found to be significant on the measured parameters. Drying of blanched thin slices of tannia cormels at relatively high temperature levels is recommended for faster and cost-effective drying of the cormels.